Sand instability under constant shear drained stress path. (1st October 2018) - Alipour, M.J.; Lashkari, A.
Abstract: Experimental findings have revealed that granular soils are vulnerable to pre-failure instability when subjected to constant shear drained (CSD) stress path. Using the concept of loss of uniqueness, it is shown that two dissimilar scenarios and accordingly, two independent criteria for granular soils in loose and dense states may lead to instability under CSD. The instability criteria are then applied in association with a state-dependent elastoplastic constitutive model taking into account possibility of elastic-plastic coupling. Numerical simulations have confirmed that instability in loose sands triggers prior to complete mobilization of the critical state stress ratio. However, instability of sands in dense state instigates at peak mobilized friction angle. A nearly unique linkage between stress ratio and state parameter at the onset of instability is predicted.